A prospective evaluation of serum methionine‐related metabolites in relation to pancreatic cancer risk in two prospective cohort studies. Issue 7 (7th April 2020) - Huang, Joyce Y.; Luu, Hung N.; Butler, Lesley M.; Midttun, Øivind; Ulvik, Arve; Wang, Renwei; Jin, Aizhen; Gao, Yu‐Tang; Tan, Yuting; Ueland, Per M.; Koh, Woon‐Puay; Yuan, Jian‐Min
Abstract : Deficiencies in methyl donor status may render DNA methylation changes and DNA damage, leading to carcinogenesis. Epidemiological studies reported that higher dietary intake of choline is associated with lower risk of pancreatic cancer, but no study has examined the association of serum choline and its metabolites with risk of pancreatic cancer. Two parallel case–control studies, one nested within the Shanghai Cohort Study (129 cases and 258 controls) and the other within the Singapore Chinese Health Study (58 cases and 104 controls), were conducted to evaluate the associations of baseline serum concentrations of choline, betaine, methionine, total methyl donors (i.e., sum of choline, betaine and methionine), dimethylglycine and trimethylamine N ‐oxide (TMAO) with pancreatic cancer risk. In the Shanghai cohort, odds ratios and 95% confidence intervals of pancreatic cancer for the highest quartile of choline, betaine, methionine, total methyl donors and TMAO were 0.27 (0.11–0.69), 0.57 (0.31–1.05), 0.50 (0.26–0.96), 0.37 (0.19–0.73) and 2.81 (1.37–5.76), respectively, compared to the lowest quartile. The corresponding figures in the Singapore cohort were 0.85 (0.23–3.17), 0.50 (0.17–1.45), 0.17 (0.04–0.68), 0.33 (0.10–1.16) and 1.42 (0.50–4.04). The inverse associations of methionine and total methyl donors including choline, betaine and methionine with pancreatic cancer risk in both cohorts support that DNA repair and methylation play an important role against the development of pancreatic cancer. In the Shanghai cohort, TMAO, a gut microbiota‐derived metabolite of dietary phosphatidylcholine, may contribute to higher risk of pancreatic cancer, suggesting a modifying role of gut microbiota in the dietary choline‐pancreatic cancer risk association. Abstract : What's new? Over half of all pancreatic cancers aren't associated with known risk factors. In this prospective study, the authors examined serum levels of three nutrients (choline, methionine, and betaine) that have been associated with reduced oxidative DNA damage and epigenetic changes such as methylation. They found that, as predicted, higher serum levels of these nutrients were correlated with lower pancreatic cancer risk. They also found that certain compounds associated with gut microbiota increased this risk. These results identify novel etiological factors that may guide future prevention strategies for pancreatic cancer.